Design and Practical Implementation of Two-Port Network Analyzer for Microwave Measurement from 200 MHz to 2.7 GHz - Chamath Kanalaka, Vithanawasam; Yi Lung, Then; Hieng Tiong, Su (2020)
Network Analyzers are commonly utilized in measuring various radio frequency (RF) and microwave measurements. In many cases Vector Network Analyzers (VNA) are available and are better suited given their ability to measure the magnitude and phase results for a device under test (DUT). These devices are, however, bulky and expensive, therefore limiting the amount of people who can have access to one of them. Due to these drawbacks, a low-cost two-port network analyzer was designed for optimum operation at frequencies from 200 MHz to 2.7 GHz. Assembly of this device brought together the combined efforts of a SynthHD signal generator, 2 AD8302 RF /IF gain/phase detectors, couplers, and a Raspberry Pi 3 Model B, which was used to program a graphical user interface (GUI), capable of plotting S-parameter readings. A commonly used error calibration method was also used to eliminate common errors.